Synthetic Studies toward Lindenane-Type Sesquiterpenoid Dimers - Yang, Li; Yue, Guizhou; Yuan, Changchun; Du, Biao; Deng, Heping; Liu, Bo (Synlett, 2014)
The key transformation for the total synthesis of the lindenane sesquiterpenoid dimers is the intermolecular Diels–Alder reaction between two lindenane-type monomers. Herein we report our efforts made on examination of the biogenetic hypothesis and the inverse-electron-demand Diels–Alder (IEDDA) reaction. The combination of Tf2NH/AlMe3 was developed to catalyze the model IEDDA reaction.
Keywords: sesquiterpene; dimer; Diels–Alder cycloaddition; total synthesis; biomimetic